Are hospital staff aware of the economic benefits of employing people with disabilities? - Machaj, Małgorzata M.; Lorkowski, Jacek; Kotela, Ireneusz (Medical Studies/Studia Medyczne, 2015)
Introduction : One of the regulations governing employment on the open labour market is the Act for vocational and social rehabilitation and employment of people with disabilities, which defines disability in the context that it impacts upon a person’s ability to work. Aim of the research : To evaluate the level of hospital staff awareness of the financial impacts of employing people with disabilities at the Central Clinical Hospital of the Ministry of the Interior in Warsaw. Material and methods: The sample and control groups consisted of people working at the hospital, comprising 247 individuals, including 194 women and 53 men, aged between 25 and 60 years. The sample group consisted of people with disabilities. The control group consisted of colleagues with disabilities, of both sexes, and of the same age range. There was also a separate sample group comprising 60 people from middle management and senior management. The sample and control groups were provided with a questionnaire about issues relating to the economic aspects of employing people with disabilities. The results were compared with data from the questionnaire for management and from hospital statistics. The methodology of mathematical statistics was used. Results : Discrepancies were found between sample and control groups, and hospital statistics pertaining to people with disabilities as employees in terms of the burden placed on the business, such as sick leave, breaks from work in the general sense, additional leave, accessing specialist tests during working hours, and earnings, in particular reimbursement of the cost of workplace equipment and funding for salaries. Conclusions: There is a significant degree of divergence between managers’ and employees’ notions of privileges for disabled workers and their actual scale. There is misunderstanding and lack of knowledge of the applicable provisions of the Act for the Vocational and Social Rehabilitation and Employment of People with Disabilities amongst a considerable portion of employees and managers.